2019
DOI: 10.1039/c9dt01160a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies on a three-membered diphosphido thorium metallaheterocycle [η5-1,3-(Me3C)2C5H3]2Th[η2-P2(2,4,6-iPr3C6H2)2]

Abstract: A three-membered diphosphido thorium metallaheterocycle complex was prepared and its reactivity was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 92 publications
2
15
0
Order By: Relevance
“…The Th−O bond lengths of 2.510(3) and 2.500(2) Å are similar to those of the Th aminopolycarboxylate complex 62 63,64 as well as double-insertion products of bis(phosphido) complexes in the literature. 40 Previously, we reported the insertion of t BuNC into the An−P bonds of ( with RNC (R = Me 3 Si, cyclohexyl, 2,6-Me 2 C 6 H 3 ) also yields phosphazaallenes. 37 The analogous product (C 5 Me 5 ) 2 U-(CN t Bu)(η 2 (N,C)-( t BuNCPMes) (5; eq 3) is obtainable in moderate yield (57%) by elimination of free H 2 PMes observed in the 31 P NMR spectrum.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…The Th−O bond lengths of 2.510(3) and 2.500(2) Å are similar to those of the Th aminopolycarboxylate complex 62 63,64 as well as double-insertion products of bis(phosphido) complexes in the literature. 40 Previously, we reported the insertion of t BuNC into the An−P bonds of ( with RNC (R = Me 3 Si, cyclohexyl, 2,6-Me 2 C 6 H 3 ) also yields phosphazaallenes. 37 The analogous product (C 5 Me 5 ) 2 U-(CN t Bu)(η 2 (N,C)-( t BuNCPMes) (5; eq 3) is obtainable in moderate yield (57%) by elimination of free H 2 PMes observed in the 31 P NMR spectrum.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…24 These complexes impart a mismatch between the hard, electropositive Lewis acidic actinide centre, and the so Lewis basic nature of phosphorus, and have been shown to afford unpredictable and unusual chemistry. [25][26][27][28][29][30][31][32][33][34] We recently showed that the U(III) complex, (C 5 Me 5 ) 2 U(THF) [P(SiMe 3 )(Mes)] reacts with Me 3 SiN 3 to form the U(VI) bis(imido) complex, (C 5 Me 5 ) 2 U(]NSiMe 3 ) 2 . 35 In order to prevent the formation of the bis(imido) complex, here, we used the mixed phosphido-methyl complexes (C 5 Me 5 ) 2 U(CH 3 )[P(SiMe 3 )(R)], R ¼ C 6 H 5 (Ph), 1; 2,4,6-Me 3 C 6 H 2 (Mes), 2.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are less inclined to form strong interactions with ligands bearing soft-donor atoms such as phosphorus. Therefore, the actinide-phosphido bond should, and has been demonstrated, be relatively reactive [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%